Seepage and Slope Stability Analysis of Myittha Multipurpose Dam Project, Gangaw Township, Magway Region, Myanmar - Hla Myat Htwe; Tun Naing (Institut Teknologi Sepuluh Nopember, 2017)
Myittha Multipurpose Dam Project is constructed on Myittha River to be implemented for hydropower production of installed power 40 MW and average annual energy 170 million kWh for regional development and irrigation network of 12,000 acres. Myittha dam has two portions of embankment: main dam (rockfill zone type) and long saddle dam (homogeneous type). The purpose of this paper is the evaluation of seepage and slope stability conditions of Myittha embankments (Myanmar) based on three different cases of operations: end of construction before filling the reservoir, steady state seepage and rapid drawdown of the reservoir. Seepage and slope stability analysis were done in two ways: analytical and computer approaches. Analytically, seepage analysis was done by using Laplace equation based on Darcy's law and slope stability analysis was done by using Ordinary Method of Slices and Bishop Simplified Method. This analytical approach was used to access based on the earthen dam details and geotechnical design parameters of embankment materials. On this research, SLOPE/W and SEEP/W soft-wares were used as computer approach. The analysis results presented in this research confirm the safety of Myittha dam against combined seepage and slope stability under all cases of operation.